FAIR TRADE CERTIFICATION PRACTICES IN THE EXPORT PROCESS OF INDONESIAN COFFEE COMMODITIES TO THE UK MARKET IN TERMS OF THE TECHNICAL BARRIERS TO TRADE (TBT) AGREEMENT - Moesviara, Arindra Driya (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2022)
The application of fair trade certification to enter specialized markets in the United Kingdom affects the coffee trade transactions exported from Indonesia to the United Kingdom. This certification then becomes a challenge and creates unnecessary trade barriers. These barriers are included in technical barriers which in international trade activities are regulated through the Technical Barriers to Trade (TBT) Agreement. Based on the results of this study are first, the application of fair trade certification on Indonesian coffee commodities that want to enter the United Kingdom specialty market is an unnecessary international trade barrier. Second, Indonesia can take legal remedies through the WTO or other efforts such as negotiation, mediation, conciliation, and arbitration for dispute resolution.